Biochemical study and digestion profile of olive oil by LipBK: Revealing the potential applications of a new acid/broad thermal range true lipase - Maria, Tainá Carolini [UNESP]; Maldaner Pereira, Pâmela A. [UNESP]; Pepe, Elisângela Soares Gomes [UNESP]; Lemos, Eliana Gertrudes de Macedo [UNESP] (Elsevier, 2025)
This study characterized a novel bacterial lipase with high biotechnological potential, focusing on industrial and environmental applications. Bacterial isolates were screened using olive oil as a substrate, and the strain with the highest hydrolytic halo was identified as Burkholderia sp. via 16S rRNA analysis. The secreted lipase was purified and exhibited high hydrolytic activity, specifically targeting long-chain fatty acids. Gas chromatography analyses confirmed its ability to hydrolyze fatty acids present in olive oil, while kinetic parameters and substrate preferences were assessed using synthetic substrates. Optimal activity was observed at pH 4.5 and temperatures between 40 and 60 °C. The enzyme demonstrated remarkable thermal stability, retaining over 78 % residual activity after 24 h at 30, 40, 60, and even 70 °C. It also displayed broad pH stability, with increased relative activity at pH 6.5 over time. LipBK showed resilience in the presence of metallic ions, salts, EDTA, and non-ionic detergents, with enhanced activity in the presence of additives like KCl, CaCl₂, and Triton X-100. These properties highlight its robustness and suitability for applications in acidic and thermally variable environments, such as biodiesel production, waste treatment, and sustainable industrial processes, contributing to global sustainability goals.
Keywords: Acidic enzyme; Bacterial lipase; Biocatalysis; Fatty acid hydrolysis; Thermostability